Assembling History in Maturin’s Melmoth the Wanderer - O’Dea, Gregory (Romanticism on the Net)

(untitled) (Université de Montréal, 2024)
In its multiple concentric and often fragmented tales, Charles Maturin’s novel Melmoth the Wanderer (1820) explores textual forms involved in the process of assembling authentic (as opposed to feigned or fictive) history. By centering all of the tales on the Wanderer, by arranging the tales in a fractured pattern that alternates oral and written sources authored by different people, and by subverting chronological sequence in presenting the tales as they are discovered and acquired, Maturin offers a group of raw historical materials that have yet to be shaped and polished into a unified history by a single guiding hand. Melmoth the Wanderer thus strips away the polished surface of reflective history to show the underlying difficulties and differences of related primary experiences and accounts. The novel as we have it forms a kind of textual palimpsest, revealing stages and challenges of the historiographical process.